A VIEW ON CURRICULUM DESIGN FOR JAPANESE LANGUAGE DEPARTMENT - Akemi Kanazawa (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2013)
According to a model curriculum presented by the Research Committee Meeting on JFL Teachers Training, the Agency for Cultural Affairs in 2000, JFL teachers training course consists of subjects mainly to cultivate international view points as well as the Japanese language teachingpedagogy. Its target is not to train Japanese students to acquire knowledge of Japanese language as a national language but to train them to acquire knowledge of JFL to be able to teach Japanese language to foreign learners. Japanese language department and international students’ education center for JFL are separate. Among international students, there are many who aim at becoming teachers of JFL. They have to study their majoring subjects together with Japanese students from freshman if they want to enter the Japanese language department. The requirement is for them to have passed Japanese language proficiency test N1-level before they can get accepted into Japanese language department. Japanese language departments in overseas universities on the other hand have dual functions; 1) for students to become a Japanese linguist and 2) to become a Japan generalist. For this reason, lots of curriculum design challenges need to be considered. In this paper, two kinds of curriculum models within Japan will be presented for reference.Challenges to define more applicable curriculum at overseas universities will also be examined.Keywords : Japanese as-a-Foreign-Language (JFL), Japanese Language Teachers’ Training Course Curriculum, International Perspective, Social-Cultural-Regional studies